2020
DOI: 10.7196/ajtccm.2020.v26i4.110
|View full text |Cite
|
Sign up to set email alerts
|

Occult pulmonary arterial hypertension in patients with previous pulmonary tuberculosis

Abstract: Background. Pulmonary tuberculosis (TB) still causes a significant public healthcare burden. Despite successful treatment, TB can lead to permanent lung damage and pulmonary hypertension (PH). PH can also occur in the absence of significant lung damage, leading clinicians to question whether pulmonary TB may cause pulmonary arterial hypertension (PAH), an entity that has not been otherwise described. Objectives. To determine the prevalence of PAH in patients previously treated for TB. Methods. We recruited 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…but the requisite right heart catheterization procedure carries risk and is expensive [6]. In suspect PH cases, noninvasive investigations like blood biomarkers, electrocardiography (ECG), chest X-ray, echocardiography, thoracic computed tomography (CT) and magnetic resonance imaging (MRI) may help corroborate the presence of morphological and/or hemodynamic changes in the heart chambers and lung vasculature consequent to PH-induced remodeling [10]. Artificial intelligence-enabled models are increasingly being used to facilitate disease diagnosis [11], especially in the classification of medical images, like CT, MRI, and X-ray [12].…”
Section: A Backgroundmentioning
confidence: 99%
“…but the requisite right heart catheterization procedure carries risk and is expensive [6]. In suspect PH cases, noninvasive investigations like blood biomarkers, electrocardiography (ECG), chest X-ray, echocardiography, thoracic computed tomography (CT) and magnetic resonance imaging (MRI) may help corroborate the presence of morphological and/or hemodynamic changes in the heart chambers and lung vasculature consequent to PH-induced remodeling [10]. Artificial intelligence-enabled models are increasingly being used to facilitate disease diagnosis [11], especially in the classification of medical images, like CT, MRI, and X-ray [12].…”
Section: A Backgroundmentioning
confidence: 99%
“…In a South African adult study, none of the patients were found to have PH by echocardiography. However, the TAPSE was reduced over time following TB infection [ 56 ].…”
Section: Epidemiologymentioning
confidence: 99%